Pemikiran Keagamaan & Kebangsaan Gus Dur - Muh - Rusli (LPPM IAIN Sultan Amai Gorontalo, 2015)
Gus Dur is a controversial and inspirational figure who has contributed brilliant ideas to religious life and nationality. To manifest religious life were fair and peaceful, the tap religion should be opened as wide as each religion entitled to the recognition of the country; Pluralism is a guarantee for every Indonesian to worship according to their religion or belief peacefully; In addition, the indigenization and contextualization of Islam, appreciate the culture and creativity of the nation itself. Indonesian Islam has own repertoire in appreciating the teachings of religion. In the context of a state, an ideology that can be accepted by all components of the nation and ensure the rights of all citizens is Pancasila; Furthermore, Democracy must be fought systemic and cultural continuously without radicalism.